Attention Residue for On-Screen Tasks - Andres Zapata (My University, 2023)
Attention equates to monetary value in the digital economy. The more attention marketers capture, the more profitable they become. This is because the Internet has been built to monetize attention. Consequently, understanding attention dynamics, especially during multitasking, is crucial. Attentional residue happens when individuals switch tasks before completing their current one, causing some cognitive energy to remain with the initial task. This reduces their performance on the subsequent task due to the distraction of the incomplete one. While attention residue has been observed in off-line modalities, attention residue has not been studied on similar or equivalent tasks on- and off-line. This study aimed to investigate attention residue in both on-screen and off-screen environments and the impact of time pressure on task performance. The study found that attention residue existed similarly in both screen modalities, suggesting that despite the constant task-switching on digital platforms, there's no discernible difference in attention residue. Time pressure was found to potentially improve performance in some scenarios which is consistent with prior research. Qualitative data suggests that participants found task interruptions frustrating, aligning with previous research. Some participants, however, derived pleasure from the challenge of the tasks, hinting at the role of dopamine and motivation in task persistence. Lastly, there seems to be an increasing acceptance of interruptions in on-screen tasks, which seems to transfer to off-screen tasks. People seem to expect interruptions in on-screen activities and this experience and expectation seems to transfer to off-line tasks suggesting that people are increasingly becoming more comfortable with interruptions.
Dissertation submitted to the Yale Gordon College of Arts and Sciences of The University of Baltimore in partial fulfillment of the requirements for the degree of Doctor of Science in Information and Interaction Design
D.S. -- The University of Baltimore, 2023
Keywords: attention spans, neurodesign, psychology, user experience design